ANALYSIS THE FACTORS AFFECTING THE ROLE OF COASTAL WOMEN’S IN FOOD SECURITY AND PREVENTING BEACH ABRASION IN INDONESIA - Pintakami, Lintar Brillian; Sugiyanto; Sukesi, Keppi; Yuliati, Yayuk (Socio-Economics/Agribusiness Department, 2024)
The aims of this research delve into the identification and analysis of key factors that influence the role of coastal women in ensuring family food security and preventing beach abrasion in Indonesia, from an ecofeminist perspective. Structural equation modeling is used to identify and analyze the influence of factors such as Role Identification (X1), Involvement and Control (X2), Coastal Women Contribution (X3), and the Influence of the Impact of the Adaptation Era (X4) on the Factors that influence the role of coastal women (Y), in food security and preventing beach abrasion in Indonesia. The research results show that coastal women farmers earn 58% more income than men. The role of coastal women in preventing beach abrasion is by 4 social movements, are Pokdarwis, Reforestation, Education, and against mangrove logging. There are 3 factors that influence the role of coastal women in food security and abrasion prevention (Y), involvement and control (X2), the contribution (X3), and the impact of the Adaptation Era (X4), with P values < alpha value (?) 0.05. The implications of this research extend beyond the Indonesian coasts, offering insights into global initiatives aimed at promoting gender equality, sustainable development, and climate change mitigation.